Bifunctional layer-by-layer metal-organic framework thin films for gas detection - Tan, Fu Lun (Nanyang Technological University, 2023)
The advancement of flexible electronics has played an important role in various fields, offering the potential for versatile applications, including wearable devices, flexible displays, and sensors. Gas sensors, in particular, have seen significant progress with the drastic development of flexible electronics. This research project explores the challenges and opportunities in developing flexible gas sensors, with a focus on the utilization of Metal-Organic Frameworks (MOFs) as gas sensing material due to their intrinsic properties of high surface area, crystallinity, porosity, adsorption capacity, and tunability. Among various MOF candidates, 2D Cu3(HHTP)2 (HHTP = 2,3,6,7,10,11-hexahydroxytriphenylene) has exhibited remarkable electrical conductivity, making it suitable for chemiresistive gas sensing. However, one of the significant challenges in employing MOFs for gas detection is their preference for rigid substrates, which limits their adaptability in flexible electronics. Hence, this project aims to bridge this gap by fabricating a flexible gas sensor based on Cu-HHTP MOF thin films. Among the different thin film fabrication techniques, layer-by-layer (LbL) assembly was chosen due to its ability to produce high-quality thin films, as in the LbL approach allows precise control over film thickness and composition. Moreover, this study delves into the fabrication process of Cu-HHTP MOF thin films on flexible substrates such as polyethylene terephthalate (PET) and polyimide (PI) with deposited interdigitated electrodes (IDEs) deposited by either thermal evaporation or screen ink printing technique, highlighting the key parameters and conditions required for successful deposition. The resulting films are characterized to ensure their structural integrity, electrical conductivity, and gas-sensing properties. In the presence of 50, 100 and 300 ppm of NH3 at room temperature, the LbL Cu-HHTP-based gas sensor have exhibited outstanding response of -16.4%, -26.1% and -33.0%, along with rapid response and recovery times of 57 s and 95 s, 32 s and 93 s, and 35 s and 130 s, respectively. Apart from gas sensing capabilities, this research has uncovered the potential for pressure sensing using the Cu-HHTP MOF thin film. Upon pressure exertion, the sensor exhibited sensitivity values of - 7.148 x 10E-4 kPa-1 in the low-pressure range (0 – 11 kPa), and -2.751 x 10E-5 kPa-1 in the high-pressure range (11 – 80 kPa), while its cycling stability over 300 pressure cycles was also demonstrated. In summary, although the pressure sensing capability may not be on par and comparable with state-of-art pressure sensors, yet this research work has demonstrated the exciting possibility of a dual-mode sensor, combining gas sensing and pressure sensing. This innovative direction provides new avenues and opens novel possibility for future research involving MOF thin films.